Transportasi dengan Perawatan Metode Kanguru untuk Menstabilkan Fungsi Fisiologis Bayi Berat Lahir Rendah - Kameliawati, Feri (Universitas Aisyah Pringsewu, 2016)
Currently the transportation of low birth weight babies (LBWB) using incubator by providing a variety of equipments to support the safety and comfort of the baby during the trip. Some effects of transport using the incubator are sleep disorder and instability temperature of the baby during the trip. This study aimed to compare the effects of transportation between KMC and cuddling. This study employed experimental approach using non equivalent control group before after design involving 34 mothers and low birth weight babies. Low birth weight babies physiologic functions for the babies were measured before and after transportation. The results showed that babies physiologic function for the babies among intervention group increased significantly (p = 0.001). There were also significant differences in babies physiologic function for the babies between intervention and control group (p = 0.001). Based on the results of this study, nurse need to implement KMC to increase the knowledge and ability of a mother in caring for LBWB (Low Birth Weight Babies).Keywords: kangaroo transportation, physiological functions LBW